2013
DOI: 10.1007/s00401-013-1166-x
|View full text |Cite
|
Sign up to set email alerts
|

Glial cell-expressed mechanosensitive channel TRPV4 mediates infrasound-induced neuronal impairment

Abstract: Vibroacoustic disease, a progressive and systemic disease, mainly involving the central nervous system, is caused by excessive exposure to low-frequency but high-intensity noise generated by various heavy transportations and machineries. Infrasound is a type of low-frequency noise. Our previous studies demonstrated that infrasound at a certain intensity caused neuronal injury in rats but the underlying mechanism(s) is still largely unknown. Here, we showed that glial cell-expressed TRPV4, a Ca(2+)-permeable me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
79
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(84 citation statements)
references
References 47 publications
5
79
0
Order By: Relevance
“…Moreover, TRPV4-mediated Ca 2+ entry is supposedly a key factor responsible for infrasound-induced glial activation and subsequent neuronal cell death [32]. In the present study, we firstly reported an over-activation of TRPV4-induced neuronal death in cerebral ischemic injury in vivo.…”
Section: Discussionmentioning
confidence: 92%
“…Moreover, TRPV4-mediated Ca 2+ entry is supposedly a key factor responsible for infrasound-induced glial activation and subsequent neuronal cell death [32]. In the present study, we firstly reported an over-activation of TRPV4-induced neuronal death in cerebral ischemic injury in vivo.…”
Section: Discussionmentioning
confidence: 92%
“…We and others have previously reported that TRPV4 is an important regulator of neuronal excitability in hippocampal neurons and that TRPV4 is expressed in both astrocytes and neurons (19,24,28,29). Therefore, we sought to determine which types of astrocytes express TRPV4 by combining in situ hybridization and immunohistochemistry in adult mouse hippocampus.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, TRPV4 ϩ astrocytes might synchronize neuronal excitability and help increase the diversity of synaptic information and brain function. Very recently, the pathophysiological function of TRPV4 in astrocytes has been reported (25,26,28). According to these reports, TRPV4 signaling in astrocytes prevents the progression of brain damage, but the physiological importance of astrocytic TRPV4 under normal conditions has remained ϩ astrocytes, shown by the blue color, are specifically localized in the brain; activation of TRPV4 in these astrocytes causes excitation in neighboring astrocytes through gap junctions and ATP release, shown as red arrows.…”
Section: Trpv4mentioning
confidence: 99%
“…TRPV4 seems to be tightly regulated by intracellular and extracellular Ca 2+ concentrations [17]. Recent study revealed that TRPV4 activation induces Ca 2+ entry and activates Ca 2+ -dependent calmodulin and PKC signaling pathways, resulting in NF-B nuclear translocation and activation; NF-B activation promotes the expression of proinflammatory cytokines IL-1␤ and TNF-␣; excessive release of IL-1␤ and TNF-␣ from glial cells causes damage to neighbouring neurons, ultimately leading to neuronal injury in rats [10]. Thus, it was hypothesized that Ca 2+ influx might be involved in the TRPV4-NO pathway through up-regulating NF-B activity in the CCD model.…”
Section: Introductionmentioning
confidence: 99%